Analisis Terhadap Kebijakan Sistem Pendidikan Agama Islam Di SMP Negeri 1 Seruyan Hilir Timur - Ajimah Suja , Nema; Muslimah, Muslimah (MADINAH, 2020)
Analysis of Islamic Education is a measure of the success of education in schools. Analysis is needed from planning, implementation, to evaluation of learning outcomes. Since the lesson plan (RPP) must be careful about the component elements related to school needs, the implementation of Islamic religious education must be relevant to the appropriate curriculum. Learning evaluation analysis is related to the evaluation of learning achievement. This study aims to analyze (1) analysis of Islamic religious education in schools (2) Implementation of Law Number 20 of 2003 concerning the National Education System on Islamic religious education (3) Problems in Islamic religious education. The method used is library research by elaborating Law Number 20 of 2003 concerning the National Education System and Government Regulation Number 55 of 2007 concerning Religious Education and juxtaposing them with relevant references. The results of this study indicate that: (1) Based on the analysis of Islamic religious education, it experienced difficulties in developing (2) Implementation of Islamic Religious Education at SMP Negeri 1 Seruyan Hilir Timur in accordance with Law Number 20 of 2003 concerning the National Education System (3) Every problem in implementing Islamic religious education has a solution in the National education sub-system.